(untitled) (Research, Society and Development, 2020)
This work shows the development of a wireless EEG signal conditioning system where they are processed by digital signal processing using LabVIEW software for the specific application of driving a cooler that controls the height of a Styrofoam ball that It is inside a clear plastic tube according to the type of alpha and beta signal that corresponds, respectively, to the state of relaxation and concentration of an individual. Wireless communication of information from biomedical hardware makes data acquisition more portable to the person who will make use of such a device. A total gain of 11326.36 [V / V] EEG signal conditioning board was obtained for signals applied at a frequency of 20 Hz and wireless data communication was successfully achieved via two NRF24L01 radio frequency modules . The prototype for the application of this wireless EEG signal conditioning system perfectly controlled the application, in other words, the height of the Styrofoam ball. And the system was validated using an Agilent 30MHz 32521A arbitrary wave generator that simulated biological signals for the 0.1 and 40 Hz frequency range.